2011
DOI: 10.1098/rstb.2011.0023
|View full text |Cite
|
Sign up to set email alerts
|

The historical biogeography of Mammalia

Abstract: Palaeobiogeographic reconstructions are underpinned by phylogenies, divergence times and ancestral area reconstructions, which together yield ancestral area chronograms that provide a basis for proposing and testing hypotheses of dispersal and vicariance. Methods for area coding include multi-state coding with a single character, binary coding with multiple characters and string coding. Ancestral reconstruction methods are divided into parsimony versus Bayesian/likelihood approaches. We compared nine methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 158 publications
(189 reference statements)
1
106
0
3
Order By: Relevance
“…According to Davies et al [57] 'these patterns reflect a complex history of speciation, extinction, anagenesis, and dispersal, which each factor probably shaped by biological traits and changed through time'. Whereas mammal assemblages are much older in Africa, Middle East, India and Himalayan regions they are relatively younger in South America and Europe [56,57,60]. The correlation between PD and FD showed that FD generally accumulates with phylogenetic age in communities on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…According to Davies et al [57] 'these patterns reflect a complex history of speciation, extinction, anagenesis, and dispersal, which each factor probably shaped by biological traits and changed through time'. Whereas mammal assemblages are much older in Africa, Middle East, India and Himalayan regions they are relatively younger in South America and Europe [56,57,60]. The correlation between PD and FD showed that FD generally accumulates with phylogenetic age in communities on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…If biogeographic history has been important in shaping mammalian diversity [52], then it should be considered alongside ecological or life-history differences when trying to understand clade-richness patterns [53]. It may also explain why ecological or life-history differences alone have so far explained little of the variance in species-richness among mammalian clades in phylogenetic comparative analyses.…”
Section: Winners and Losers: Pinpointing Shifts In Diversification Ratementioning
confidence: 99%
“…through competition or predation). At a global scale, it is clear that evolutionary biogeography places strong constraints on regional abundance and species richness [41,42], but it is not clear whether this kind of nonindependence translates into the statistical independence assumed by McGill [8].…”
Section: (D) Species Abundance Distributionmentioning
confidence: 99%
“…(c) Temporal patterns in biodiversity Diversification rates across mammals have not been equal [41,98], which has led to significant imbalance in the distribution of species at nodes in the mammalian phylogenetic tree over time. This diversification rate variation leads to the distribution of species among higher taxa following a hollow curve, i.e.…”
Section: Other Mammalian Biodiversity Patternsmentioning
confidence: 99%